Cantadoras e repentistas do século XIX: a construção de um território feminino - Francisca Pereira dos Santos (Estudos de Literatura Brasileira Contemporânea)
Tus article discusses women’s presence in the Field of improvised singing during the XIXth century, a part still little studied in historiography, given, among other issues, the existence of a discourse saying that women did not belong to this world. On the contrary, we verify that women singers and improvisators always sung and took active part in this field. In this sense, to bring these forgotten voices, we started with a bibliographical research departing from the contribution of folklore scholars, the only heap where we can still find the vestiges of their presences